Assessment of fraud risk performance: interaction effects of brainstorming and task structure of government auditors / Mohd Daniel Mohd Nassir … [et al.] - Mohd Nassir, Mohd Daniel; Mohd Sanusi, Zuraidah; Ghani, Erlane K.; Prabowo, Hendi (Universiti Teknologi MARA Cawangan Selangor, 2016)
The inability of the government auditor to detect misstatement, especially on fraud risk may expose the auditors to lawsuits which consequently lead to bad reputation. However, task structure may also affect the performance of fraud risk assessment. Fraud risk assessment task can be classified into structured, less structured and unstructured task. Fraud risk assessment in the structured task involves assessment of fraud risk using tests of control whilst less structure task used substantive test to identify fraud risk. In practice, auditors would perform both tasks and therefore, task structure becomes the within-subject in this study. This study examines the direct and interaction effects of brainstorming and task structure against fraud risk assessment performance. The 2 X 2 factorial design was employed, and a total of 151 government auditors participated in this study. The government auditors assessed the fraud risk based on individual or on group basis. The results show that brainstorming and task structure have a direct impact on fraud risk assessment performance. However, the results show no significant interaction between brainstorming and task structure. Although brainstorming improves fraud risk assessment performance, task structure proves otherwise. The findings in this study provide insights on the importance of brainstorming and task structure for government auditors.